Knowledge, attitude and practice (KAP) associated with calcium carbide (CaC2) used for fruit ripening among mango farmers, farm workers and fruit traders - Ismail, Noor Shaeda; Rasdi, Irniza; Praveena, Sarva Mangala; Zainal Abidin, Emilia (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Calcium Carbide (CaC2) use for fruit ripening become dubious in recent years when various health related issues began to arise. This study aims to assess knowledge, attitude and practises (KAP) and health related to CaC2 among mango farmers, staff/workers working in mango farms and fruits traders in Perak, Kedah and Perlis. Methods: All potential respondents in the study locations was invited to participate. Yes-no questions were used to assess KAP while structured questions were used to obtain socio-demographic data through face-to face interview. Results: The response rate for this study was 67.8% (n = 200). All respondents were male with the average age of 40.45 years old. Majority of them (67.5%) completed secondary school as their highest education level. Overall, less than half of the total respondents have appropriate KAP. Only job tenure significantly associated with the knowledge on the type of suitable PPE (χ2= 16.421). Respondents with secondary or tertiary school of education level (χ2= 9.154) and those with 1-5 years of job tenure (χ2= 10.932) showed significantly better attitude on CaC2 handling. Also, the total scores of knowledge significantly associated with attitude (χ2= 26.801) and application of glove (χ2= 12.551). In multiple logistic regression only respondents with the knowledge on type of PPE (OR = 6.30) will persist to use CaC2. Conclusion: The KAP related to CaC2 among respondents is low and their knowledge was significantly associated with their attitude and practice. Therefore, effective training and communication approach is warranted.